Avaliação do acometimento cardíaco em camundongos BALB/C infectados por Paracoccidioides brasiliensis - Junnia Alvarenga de Carvalho Oliveira (2017)
Paracoccidioidomycosis is a systemic disease, endemic in Latin America, caused by dimorphic fungi of Paracoccidioides genus. Even though the primary pathway of infection is pulmonary, by inhalation of conidia, several anatomical sites may affected by lymphoematogenic dissemination, including the heart. Studies demonstrate the complexity of the P. brasiliensis caused disease and reveal a necessity to investigate the microorganism infection sites, so the involvement may be underdiagnosed. The aim of this work was to identify and characterize fungal colonization in the heart of P. brasiliensis infected mice. BALB/c mice were infect with virulent Pb18 strain of P. brasiliensis that euthanized at 7, 15, 30 and 60 days after infection. The heart was removed and used for the following experimental procedures: fungi recovery culture medium; histological analysis using different methodologies to detect fungi and inflammatory reaction in cardiac tissue; nested PCR to evidence fungi genetic material in the tissue; quantification of the cytokines IL-4, IL-6, IL-10 and TNF-α cytokines in the tissue by ELISA method. Some animals were immunosuppressed by gamma radiation and euthanized after 7 days of infection to fungi recovery of cardiac tissue in culture medium and rate survival of the animals. Fungal cells recovered from cardiac tissue were viable and virulent. Visualization of the amplicon of the fungus by the PCR technique confirmed the presence of P. brasiliensis in cardiac tissue. As histological analyzes revealed a granulomatous inflammatory infiltrate presenting collagen fibers around the fungi corroborating the ELISA findings that revealed elevated levels of TNF-α in cardiac tissue. These results demonstrated fungi colonization and development of inflammatory reactions in the heart of P. brasiliensis infected mice, characteristic of Paracoccidioidomycosis.